2021
DOI: 10.1007/s42995-021-00117-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural diversity and biological activity of natural p-terphenyls

Abstract: p-Terphenyls are aromatic compounds consisting of a central benzene ring substituted with two phenyl groups, and they are mainly isolated from terrestrial and marine organisms. The central ring of p-Terphenyls is usually modified into more oxidized forms, e.g., para quinone and phenols. In some cases, additional ring systems were observed on the terphenyl-type core structure or between two benzene moieties. p-Terphenyls have been reported to have cytotoxic, antimicrobial, antioxidant and α-glucosidase inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 93 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…According to numerous studies (Cao et al 2020 ; Hai et al 2021 ; Meng et al 2021 ; Song et al 2018 ; Wang et al 2018 ; Zhou et al 2022 ), marine-derived fungi have demonstrated to be a significant source of natural products with diverse chemical structures such as alkaloids, phenols, polyketides, terpenoids, and benzenes, which have remarkable potential as drug candidates in clinical applications (Carroll et al 2022 ; EI-Kashef et al 2019 ). Verrucosodin ( 4 ), the first example of a rarely reported class of methylated α -pyrone polyketide derivative, was initially isolated from Penicillium verrucosum var cyclopium in 1983 (Burka et al 1983 ) and was found to possess the inhibitory activity for the expression of glucose-regulated protein 78 (GRP78) under strict hypoglycemic conditions and led to selective cell death of glucose-deprived HT-29 human colon cancer cells (Park et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to numerous studies (Cao et al 2020 ; Hai et al 2021 ; Meng et al 2021 ; Song et al 2018 ; Wang et al 2018 ; Zhou et al 2022 ), marine-derived fungi have demonstrated to be a significant source of natural products with diverse chemical structures such as alkaloids, phenols, polyketides, terpenoids, and benzenes, which have remarkable potential as drug candidates in clinical applications (Carroll et al 2022 ; EI-Kashef et al 2019 ). Verrucosodin ( 4 ), the first example of a rarely reported class of methylated α -pyrone polyketide derivative, was initially isolated from Penicillium verrucosum var cyclopium in 1983 (Burka et al 1983 ) and was found to possess the inhibitory activity for the expression of glucose-regulated protein 78 (GRP78) under strict hypoglycemic conditions and led to selective cell death of glucose-deprived HT-29 human colon cancer cells (Park et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diarylcyclopentenones, which possess a rare class of a tricyclic 6/5/6 system, could also belong to p-terphenyl derivatives from a biosynthetic perspective. To date, more than 230 natural products containing p-terphenyl have been unearthed in nature, among them many p-terphenyls were isolated from fungi, only a few were discovered from Streptomyces species [1][2][3][4]. Meanwhile, these types of compounds exhibit a broad spectrum of bioactivities, including antitumor [5,6], antibacterial [7,8], antioxidant [9][10][11][12], immunosuppressive [13], and antithrombotic activities [14].…”
Section: Introductionmentioning
confidence: 99%